Pengaruh Dosis Pupuk Kompos Kelinci dan NPK Mutiara Terhadap Pertumbuhan dan Hasil Tanaman Mentimun (Cucumis sativus L.) - Made Ary Sastrawan; Yohanes Parlindungan Situmeang; Ketut Sunadra (Fakultas Pertanian, Universitas Warmadewa, 2020)
This study aims to determine the effect of rabbit compost and NPK Mutiara dosage and their interactions on the growth and yield of cucumber plants. The design used in this study was a randomized block design (RBD) with 2 factorials. The first factor is the provision of rabbit compost fertilizer with 3 levels (0, 10, and 20 ton ha-1) and the second factor is giving NPK Mutiara fertilizer with 3 levels (0, 150, and 300 kg ha-1). The interaction between rabbit compost and pearl NPK had no significant effect on all observed variables except for the fruit fresh weight variable, which had a significant effect. The treatment of rabbit compost (K) had a significant to very significant effect on all observed variables, except for the variable number of fruits per plant and staged oven dry weight, which had no significant effect. The treatment of NPK pearl fertilizer (M) statistically has no significant effect on all observed variables, except for the variable fresh weight of fruit and dry weight of the staged oven which has a significant effect. The highest fruit fresh weight was obtained at the interaction between the dose of 20 ton ha-1 rabbit compost with a dose of 300 kg ha-1 NPK pearl of 6322.42 g or an increase of 150.36% when compared to the interaction between without rabbit compost and NPK pearl of 2525.37 g. Provision of rabbit compost of 20 ton ha-1 and NPK pearl 300 kg ha-1 can be suggested to increase the fresh fruit weight of cucumber plants.